Oscillation Criteria for a Class of Second-Order Neutral Delay Dynamic Equations of Emden-Fowler Type - Zhenlai Han; Tongxing Li; Shurong Sun; Chao Zhang; Bangxian Han (Abstract and Applied Analysis)
We establish some new oscillation criteria for the second-order neutral delay dynamic equations of Emden-Fowler type, [a(t)(x(t)+r(t)x(τ(t)))Δ]Δ+p(t)xγ(δ(t))=0, on a time scale unbounded above. Here γ>0 is a quotient of odd positive integers with a and p being real-valued positive functions defined on 𝕋. Our results in this paper not only extend and improve the results in the literature but also correct an error in one of the references.